2012
DOI: 10.2519/jospt.2012.3838
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Movement Screen: A Reliability Study

Abstract: More than 10 000 Americans seek medical treatment for sports, recreational activity, and exercise-related injuries on a daily basis. 20 Researchers have estimated that 50% to 80% of these injuries are overuse in nature and involve the lower extremity. 1,11,25 In the military, physical training and exercise-related injuries account for 30% of hospitalizations and 40% to 60% of all outpatient visits, with 10 to 12 injuries per 100 soldier-months.12 Although the risk of musculoskeletal conditions and injuries is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(215 citation statements)
references
References 20 publications
(37 reference statements)
8
186
1
7
Order By: Relevance
“…In addition to these measures, results from the most recent Army Physical Fitness Test was collected. Further description of these tests is outlined subsequently and has been reported previously [33,39,40].…”
Section: Baseline Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these measures, results from the most recent Army Physical Fitness Test was collected. Further description of these tests is outlined subsequently and has been reported previously [33,39,40].…”
Section: Baseline Data Collectionmentioning
confidence: 99%
“…The standard 0 to 3 score on the Functional Movement Screen was used for testing where a 0 indicates pain during the test, a 1 indicates complete inability to perform the test, a 2 indicates ability to perform the test with compensation, and a 3 indicates the ability to perform the test in the most challenging fashion without any movement deviations. The Functional Movement Screen has good interrater (ICC = 0.74) and intrarater (ICC = 0.76) reliability with trained raters in military populations [40]. Joint clearing tests are part of this screen and were performed to determine if end range pain was present in the lower extremity, trunk, or shoulder complex.…”
Section: Baseline Data Collectionmentioning
confidence: 99%
“…A major advantage of FMS is its high reproducibility. The results can be used to plan prevention -and also rehabilitation, if necessary -in order to address issues with a particular function of the body [34,35]. The usefulness of FMS is evidenced by a large number of studies where this test has been applied to assess the risk of body injury, the effectiveness of the preventive measures undertaken, or the impact of training on health [36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Each of the components is scored from 0 to 3, where a '0' score is given when there is presence of pain associated with the movements. An intrarater test-retest and interrater reliability study of FMS was conducted by [14] and it was found that the composite score shows moderate to good reliability with acceptable levels of measurement error.…”
Section: Methodsmentioning
confidence: 99%